Strategi Pemasaran Guna Meningkatkan Penjualan Benih Jagung Manis Madu-59 F1 Di Kecamatan Karangploso, Malang Jawa Timur (Marketing Strategy To Increase Sales Of Sewet Corn Seeds Honey-59 F1 In Karangploso District, Malang East Java) - Muhammad Ridwan; Rinawati Dewi; Damar Prakoso; Ida Syamsu Roidah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The demand for sweet corn continues to increase in line with the rapid development of the food industry. Therefore, every company must be able to develop a strategic business plan to achieve the company's goals, whether short-term, medium-term, or long-term. One Day Promotion is one of the promotional activities with a gift given for every purchase of MADU-59 F1 sweet corn seeds, which is held at the Agricultural Store. This activity aims to know, implement, and identify the effectiveness of One Day Promotion (ODP) to increase sales. This activity was conducted in Karangploso, Malang, East Java, using two methods: collecting primary data through interviews, observations, recordings, and documentation, as well as collecting secondary data through literature references such as journals, books, and the internet. The One Day Promotion activity was conducted at three agricultural stores in Karangploso, Malang, East Java. This activity is considered effective in increasing brand awareness and serving as an educational medium for farmers to know the advantages of MADU-59 F1 sweet corn seeds. Additionally, the One Day Promotion activity aims to help achieve the company's goal of increasing product sales volume. With the One Day Promotion strategy, it will attract consumer interest and provide satisfaction to consumers, thus accelerating and expanding the market for MADU-59 F1 sweet corn seeds.